FORMULATION, STABILTY TEST AND ENZYME ACTIVITY TEST TYROSINASE OF CREAM PEPARATIONS FROM HERENDONG FRUIT EXTRACT(Melastoma affine D. Don) - Zuraida Sagala; Kurnia Telaumbanua (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2020)
One way to prevent or inhibit melanin formation is by inhibiting tyrosinase activity (Lloyd,2011). Tyrosinase enzyme is an enzyme that plays a role in the formation of skin pigments or known as melanogenesis. In the process of melanogenesis, the enzyme tyrosinase acts as a catalyst in two different reactions, namely the hydroxylation process of tyrosine to dihydroxy-phenylalanine (L-DOPA) and oxidation of L-DOPA to quinone DOPA. Tyrosinase in skin tissue is activated by solar UV radiation so that it accelerates the process of melanin production (Fais et al.  2009).  This  study  was  conducted  to  determine  the  stability,  effectiveness  of  cream preparations from ethanol extracts of Harendong fruit (Melastoma affine D. Don) as tyrosinase enzyme inhibitors so it can be used as a cosmetic ingredient for whitening or skin lightening. Results Cream with variants of Harendong (Melastoma affine D. Don) ethanol extract was physically stable and formulated with organoleptic test, homogeneity, viscosity, mechanical test, pH, cycling test, and irritation test. Type M / A cream preparations from ethanol extract of Harendong fruit (Melastoma affine D. Don) have a strong / moderate tyrosinase enzyme inhibitor activity with IC50 values of F1 (1%) of 526,192 ppm, F2 (1.5%) ) amounted to 317,534 ppm and F3  (2%)  amounted  to  128,523  ppm.  Keywords: Foemulation,  stability test, activity test, tyrosinase enzyme, herenong fruit (Melastoma affine G.Don)